Beispiel Nr: 01
$\text{Gegeben:}\\ \text{Gerade 1: } \vec{x} =\left( \begin{array}{c} a1 \\ a2 \\ a3 \\ \end{array} \right) + \lambda \left( \begin{array}{c} b1 \\ b2 \\ b3 \\ \end{array} \right) \\ \text{Ebene: } n1 x_1+n2 x_2+n3 x_3+c1=0 \\ \\ \text{Gesucht:} \\\text{Lage der Geraden zur Ebene.} \\ \\ \textbf{Gegeben:} \\ \text{Gerade: } \vec{x} =\left( \begin{array}{c} 6 \\ 1 \\ 2 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 1 \\ 6 \\ 8 \\ \end{array} \right) \\ \text{Ebene: } 7 x_1+1 x_2+4 x_3+8=0 \\ \\ \\ \textbf{Rechnung:} \\ \text{Gerade: } \vec{x} =\left( \begin{array}{c} 6 \\ 1 \\ 2 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 1 \\ 6 \\ 8 \\ \end{array} \right) \\ \text{Ebene: } 7 x_1+1 x_2+4 x_3+8=0 \\ \begin{array}{ccc} x_1=& 6 &+1\lambda \\ x_2=&1 &+6\lambda \\ x_3=&2 &+8\lambda \\ \end{array} \\ 7( 6+1\lambda) +1(1+6\lambda) +4 (2+8\lambda)+8=0 \\ 45\lambda+59=0 \\ \lambda=\frac{-59}{45} \\ \lambda= -1\frac{14}{45} \\ \vec{x} = \left( \begin{array}{c} 6 \\ 1 \\ 2 \\ \end{array} \right) -1\frac{14}{45} \cdot \left( \begin{array}{c} 1 \\ 6 \\ 8 \\ \end{array} \right) \\ \text{Schnittpunkt: }S(4\frac{31}{45},-6\frac{13}{15},-8\frac{22}{45}) \\ $